Attitude of Student Openness toward Relational Thinking - B A Saputro; D Suryadi; R Rosjanuardi; B G Kartasasmita (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The purpose of this study on determine the attitude of student openness on relational thinking in terms of arithmetic ability. Five questions were given to three students through ainterview. The interview results were analyzed to determine the students' openness on relational thinking that has been previously taught. Students who have high and low arithmetic ability have an openness to relational thinking, while students moderate are reluctant to accept relational thinking.